Development of augmented reality integrated physics e-worksheet to improve students' problem-solving skills - Rosalita Anggi Suryanto; Poppy Sari Dewi; Dadan Rosana (Momentum: Physics Education Journal, 2022)
The STEM approach through the augmented reality usage can provide visualization to students in online learning. The purposes of this research are to develop Physics E-Worksheet based on STEM using augmented reality system, and to improve the problem-solving skills of high school students on Momentum and Impulse material. The type of research used is research and development (R&D) with a 4D model (define, design, develop and disseminate). This study involved 24 students as a field trial class and 31 students in class X as a field operational class. The results of this study are: This Physics AR E-Worksheet is valid and reliable for use in the physics learning process for Momentum and Impulse material based on the results of validation analysis using an average value of a scale of four with a score of 3.73 in very good criteria. The results of the Paired T-Test analysis showed the value of Sig. 0.00, so that there is an effect of using AR Physics E-Worksheet on improving problem-solving skills of high school students. The score of Normalized Gain obtained 0.77 in high category improvement. The results showed that the AR Physics E-Worksheet was effective in improving problem solving skills so that it could be used as a learning medium for the Momentum and Impulse topic by class X science students.